2019
DOI: 10.1038/s41597-019-0187-2
|View full text |Cite
|
Sign up to set email alerts
|

A dataset of cetacean occurrences in the Eastern North Atlantic

Abstract: The CETUS project is a cetacean monitoring program that takes advantage of cargo ships to undertake survey routes between Continental Portugal, Macaronesian archipelagos and West Africa. From 2012 to 2017, over 50 volunteers participated in the program, actively surveying more than 124.000 km, mostly beyond national jurisdictions in the high seas, for which little or no previous data existed. In total, the collection comprises 3058 georeferenced transect lines and 8913 positions, which are associated with 2833… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Dedicated trained observers followed a standardized protocol for cetacean monitoring along line‐transect surveys, aboard cargo ships from TRANSINSULAR (Correia, Gandra, et al, 2019; Correia et al., 2015), which were used as OPOs. The company operates routes for cargo transport between Continental Portugal and Macaronesian archipelagos, with stopovers in the north‐west Africa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dedicated trained observers followed a standardized protocol for cetacean monitoring along line‐transect surveys, aboard cargo ships from TRANSINSULAR (Correia, Gandra, et al, 2019; Correia et al., 2015), which were used as OPOs. The company operates routes for cargo transport between Continental Portugal and Macaronesian archipelagos, with stopovers in the north‐west Africa.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, data collected are effort‐based as the survey effort is also recorded, which is fundamental to provide reliable information on distribution and relative abundance, especially when effort is highly heterogeneous and survey activity is conditioned by the weather (Correia et al., 2015; Evans, Hammond, 2004). The project has resulted in a large dataset of cetacean occurrence records across the ENA (Correia, Gandra, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The datasets presented in this study can be found in online repositories. The names of the repository/repositories and accession number(s) can be found below: The dataset analysed for this study can be found openly available in VLIZ, distributed by OBIS and EMODnet at https://doi.org/10.14284/350associated data paper (Correia et al, 2019a). Supplementary Material is also provided.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…In this study, we aimed to relate habitat characteristics to the distribution of the eight most frequently sighted cetacean species within the eastern North Atlantic, by using ecological niche models, at basin-scale, with data collected between 2012 and 2017 from OPOs along long-distance routes (CETUS Project; Correia et al, 2019a). A description of the spatial and temporal distributions of all cetacean species sighted is presented in Correia et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Any advances are made in research about cetaceans every day, underlining the richness of these marine mammals in the waters of the Canary Islands (Aguilar de Soto et al, 2001;Pérez-Vallazza and Haroun, 2005;Pérez-Vallazza et al, 2008;Fernández et al, 2009;Carrillo and Ritter, 2010;Fais et al, 2016;Puig-Lozano et al, 2020) and in the Macaronesian region (Carrillo, 2007;Alves et al, 2015;Correia et al, 2019). Unfortunately, only a few research articles have been published on the spatial and temporal distribution of these animals, that too only for some specific areas in the waters of the Canary Islands; this study is the first in our knowledge to show the general spatial distribution of cetaceans in the waters of the whole Canary archipelago.…”
Section: Introductionmentioning
confidence: 99%